곤혹스러운 교재: 문선집 다시 읽기 - 봉준수(Bong Joon-Soo) (영미연구, 2017)
『노튼영문학선집』이나 『미국문학의 전통』과 같은 대형 문선집들은 그 부피, 무게, 가격, 그리고 구성 등에 있어서 교수자와 학생 모두에게 곤혹감을 안겨준다. 자주 지적되는 바이지만 문선집이 수록 작품들을 결정하는 기준은 언제나 논란의 소지를 포함하게 되고, 원문의 맥락에서 떨어져 나온 발췌문을 종종 싣게 되는 등 여러 가지 불만족스러운 부분들을 생래적으로 지니게 된다. 그러나 문선집을 교재로 사용하는 교수자들은 그것의 단점 또한 활용하려는 적극성이 필요하다고 본고에서는 제안한다. 그러자면 우선 문선집의 편집에 영향을 끼치는 요소들을 두루 살펴보아야 하고, 또한 언제나 논쟁의 대상으로 남아있는 ‘정전’이라는 개념과 문선집을 서로 연관시켜 고찰해야 할 것이다. 문선집을 교재로 사용할 때는 단지 수록되어 있는 작품만 읽을 것이 아니라, 그것이 어떤 구성 원리에 의거하여 가령 어떻게 젠더나 인종, 다문화주의와 같은 문학 외적 요소들과 교호작용을 해가면서 만들어지는지 검토해야 할 것이다. 이는 ‘제도’로서의 문학을 뚜렷하게 드러내는 작업이며, 이러한 작업은 궁극적으로 교수자의 위치 역시 문선집이나 정전과 마찬가지로 역사적, 문화적 맥락에서 구축되는 것임을 드러내게 될 것이다. Voluminous, weighty and exorbitant, and almost never read in entirety, big commercial anthologies have long remained a pedagogical challenge. True, they represent a category of literary publication fraught with negative implications, but this paper aims to suggest some of the ways to use these perplexing textbooks in a productive way. It is pedagogically viable to teach students how contingently and inevitably anthologies are “constructed” both internally and externally, and how influential the concepts of gender, race and multiculturalism have been in the canon formations for the last forty years. Consistent efforts need to be made in order to lead the uninitiated to be more self-conscious about literature as an institution—that is, something constructed, contingent, and thus changeable. Further, to explore the constructedness of literary institutions, including anthologies and canons, will result in a meaningful destabilization of the instructor’s own position. KCI Citation Count: 0